Phenolic compounds content and antioxidant activity of ‘Galaxy’ apples stored in dynamic controlled atmosphere and ultralow oxygen conditions - Stanger M.C.* (2018)
© 2018The effects of a dynamic controlled atmosphere, monitored by the respiratory quotient (DCA-RQ) or chlorophyll fluorescence (DCA-CF), and ultralow oxygen (ULO) conditions on the quality, individual (IPC) and total (TPC) phenolics content and total antioxidant activity (TAA) of the peel and fleshflesh tissues of ‘Galaxy’ apples have been evaluated. DCA, and especially DCA-RQ, resulted in higher IPC in the peel, with higher contents of chlorogenic acid and procyanidin B1. In the flesh, the IPC and TPC was higher for DCA-RQ and DCA-CF than in all ULO conditions. Highest chlorogenic acid, epicatechin and catechin contents were found in DCA-RQ stored fruit.